A test of Darwin's 'lop‐eared' rabbit hypothesis. (28th July 2016) - Cordero, G. A.; Berns, C. M.
Abstract: Integration of evolutionary and developmental biology has stimulated novel insights on the origins and maintenance of phenotypic variation. For instance, phenotypic accommodation predicts that trait covariance originates via a novel developmental input caused by genetic change in one trait, but not the other. Darwin provided a striking example of this process in the 'lop‐eared' rabbit by demonstrating that artificial selection for long external ears induced variation in the external auditory meatus. Although this intriguing pattern has been interpreted as evidence of phenotypic accommodation, it is unclear whether it exists and, if it does, whether it is selectively maintained in nature. To address this concern, we examined trait covariance in natural woodrat populations that have likely undergone selection for long ears. We demonstrated a remarkably similar covariance pattern as in the 'lop‐eared' rabbit, which was associated with climatic variables along a steep arid‐to‐moist longitudinal gradient. Thus, our results suggest that trait covariance is likely a correlated response to selection. We relate these findings to potential origins of trait covariance owing to altered developmental interactions, such as in phenotypic accommodation. Additional evidence is needed to clarify how phenotypic accommodation and correlated selection promote and maintain trait covariance in natural populations. Nonetheless, our study is the first to support a classic Darwinian example concerning domestication and natural selection.